Stability Studies on Refined Soybean Oil Stored in Various Conditions: Stability Study of Stored Soybean Oil (Biological Sciences - PJSIR, 2009)
The 12 months stability study of freshly produced refined soybean oil revealed that refined soybean oil stored in plastic containers in dark was more hydrolytically and oxidatively stable than that stored in other containers in light condition. There was no significant difference at P < 0.05 in free fatty acids and acid value of oil stored under light and dark conditions in tin and glass containers but there was significant difference at P < 0.05 in peroxide value of oil stored in light and dark conditions in all the storage containers. Light increased the degree of oxidative rancidity of refined soybean oil, the most in tin containers, followed by glass containers and the least in plastic containers.